(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Background of the Study Barangay is a place where you would know about issues, information, and the like regarding its constituents. The Barangay Batasan is in charge of organizing development projects and programs within its boundaries, carrying out policies and activities in the community, and providing the inhabitants with basic services that barangay officials, personnel, and members of the Lupong Tagapamayapa and staff are expected to carry out their prescribed obligations and responsibilities at the local level by upholding the laws, executing pertinent initiatives, and advancing the welfare of all. Barangay Officials in implementing ordinances and administrative code of the barangay (3.59), follow the instruction order to ensure the safety of the people in their barangay and the barangay responds immediately when called for help (3.57), help the Barangay Officials prevent crimes and promote peace and order (3.54), conducts planning and strategical method to promote public safety (3.52), and initiates teamwork in preventing or otherwise minimizing the commission of crime in the barangay (3.49).